2009
DOI: 10.1177/1468796809103459
|View full text |Cite
|
Sign up to set email alerts
|

Visibility, settlement success and life satisfaction in three refugee communities in Australia

Abstract: This article explores settlement experiences of three refugee populations — ex-Yugoslavs, black Africans and people from the Middle East — who recently (1990s—2000s) arrived in Western Australia. Settlement success and life satisfaction are investigated in connection with the three groups' racial and cultural visibility in the host milieu and an endemic loss of occupational and social status. Data were collected through a survey of 150 refugees and the interpretation of statistical outputs was aided by follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(133 citation statements)
references
References 31 publications
5
123
0
Order By: Relevance
“…In line with previous research (see Colic-Peisker, 2009;Colic-Peisker & Tilbury, 2006), participants felt disadvantaged in the employment market for a multitude of reasons, such as educational qualifications not being recognized, lack of local work experience, no local references, no copies of certificates, and differences in job-seeking practices (e.g., having to write a resume and addressing selection criteria). According to Asif (62,unemployed), within the local Somali community, up to 80% of young Somalis (20-40 age group) were cab drivers, not out of choice, but out of necessity.…”
Section: Themes From Somali Male Focus Groupssupporting
confidence: 48%
See 1 more Smart Citation
“…In line with previous research (see Colic-Peisker, 2009;Colic-Peisker & Tilbury, 2006), participants felt disadvantaged in the employment market for a multitude of reasons, such as educational qualifications not being recognized, lack of local work experience, no local references, no copies of certificates, and differences in job-seeking practices (e.g., having to write a resume and addressing selection criteria). According to Asif (62,unemployed), within the local Somali community, up to 80% of young Somalis (20-40 age group) were cab drivers, not out of choice, but out of necessity.…”
Section: Themes From Somali Male Focus Groupssupporting
confidence: 48%
“…(p. 176) 10 This paper applies visible difference to examine the challenges faced by Somali former refugees on employment. The relevance of visibility in terms of settlement is that it often marks out refugees (as well as other visible migrants) for differential and sometimes discriminatory treatment in the workforce and other societal domains of their host countries (Colic-Peisker, 2009). ColicPeisker and Tilbury's (2007) investigation into the effect of visible difference on employment found that African minority groups (from Somalia, Sudan, Ethiopia, and Eritrea) suffered high levels of unemployment based on race, religion, and ethnic origin, with multiple narratives reflecting racial discrimination in the workforce.…”
Section: Visible Differencementioning
confidence: 99%
“…communities; due to their distinctiveness in the Australian social context of a predominantly white, Christian, English-speaking population (Colic-Peisker 2009). It is the inference potential of this visibility that is the interest of this paper, in particular the potential of some visible religious markers to be perceived as projecting an underlying essence about the group that irrevocably defines who the group is, what they think and what they do ).…”
Section: Editorial Cartoons and The Visual Representation Of Essentialimentioning
confidence: 97%
“…Australia accepts around 13,000 refugees a year, and began accepting Humanitarian refugees in 1938 when it offered protection to Jews escaping Nazi Germany. However, it was not until 1975, and the end of the Vietnam war, that the composition of the refugee intake, in line with the focus of the Humanitarian program, shifted from the culturally familiar to the culturally distant (Colic-Peisker 2009;Hanson-Easey and Augoustinos 2010).…”
Section: Editorial Cartoons and The Visual Representation Of Essentialimentioning
confidence: 99%
“…Turning to international studies on the general well-being of refugees and asylum-seekers, the following emerged in studies undertaken in developed countries, including the USA, (Meredith, 1984;Tran & Wright, 1986) and Australia (Colic-Peisker, 2009). The study by Meredith (1984) considered the subjective well-being of Lao Hmong refugees and asylum-seekers in Nebraska, while the study by Tran and Wright (1986) investigated the subjective well-being of Vietnamese refugees in the USA.…”
Section: Factors Influencing the General And Subjective Well-being Ofmentioning
confidence: 99%